Preparation, Crystal structure and Luminescence Properties of Lanthanide Complexes with 2,4,6-tri(pyridin-2-yl)-1,3,5-triazine and Organic Carboxylic Acid - Jingjing Li; Xueqiong Zhang; Bin Yue; Ailing Wang; Haibin Chu; Yongliang Zhao (Crystals, 2017)
Five crystal complexes {[Eu2(TPTZ)2(mNBA)6(H2O)2]·2CH3OH}n (1), [Eu(TPTZ)(CF3COO)(H2O)5]·Cl2·CH3CH2OH (2), {[Yb2(TPTZ)2(BDC)3]·2H2O}n (3), [Yb(TPTZ)Cl(H2O)4]·Cl2 (4) and [Er(TPTZ)(TTA)Cl2] (5) (mNBA = m-nitro benzoate, BDC = terephthalate, TTA = thenoyltrifluoroacetone, TPTZ = 2,4,6-tri(2-pyridyl)-1,3,5-triazine) have been synthesized. The single X-ray diffraction reveals that TPTZ is mainly in the trident coordination mode and organic aromatic carboxylic acids are in the multiple coordination modes in the crystals. The composition of solvents, reaction temperature and reactant ratios all affect the composition and structure of the formed crystals. Crystals 1 and 3 belong to triclinic system, while the other three belong to monoclinic system. Among them, Crystal complexes 1 and 3 are coordination polymers. The other three crystals are mononuclear complexes with LnШ ions in the asymmetric environment. Both of the Crystal complexes 1 and 2 show strong luminescence emissions of Eu3+. The luminescence lifetimes of the two complexes are 0.761 ms and 0.447 ms, respectively. In addition, their luminescence quantum efficiencies are 25.0% and 16.7%, respectively.